Implementasi Pendidikan Agama Kristen Berbasis Formasi Rohani bagi Generasi Z Masa Kini - Fify Joseph (Sekolah Tinggi Teologi Blessing Indonesia Makassar, 2021)
The existence of the Implementation of Spiritual Formation-Based Christian Religious Education in every realm of education, makes a person's spirituality move forward and continue to grow and level up. This means that Christian education that takes place is not merely knowledge but there is active action instead to become doers of God’s Words.A spiritual formation that is applied in the life of a believer will help him or her to sharpen his/her spirituality and strength of faith so that he/she is able to overcome the desires in the flesh that are contrary to the will of the Father. Of course, this is not just a response, but spiritual practices instead that are continuously practiced in daily life. If not, it will experience spiritual stagnation or dryness and even spiritual death.This study uses a qualitative research method with a literature study, where the author will elaborate on the characteristics of Generation Z through various supporting literature, and propose the application of Spiritual Formation-Based Christian Religious Education for Generation Z in preparing them to face the challenges of today's faith, so that conclusions can be drawn on the Implementation of Religious Education. Spiritual Formation-Based Christianity is a teaching or learning process that focuses on the continuous application of spiritual discipline through mentoring and discipleship, with the aim of having a character and personality similar to Jesus Christ in his daily life. AbstrakAdanya Implementasi Pendidikan Agama Kristen Berbasis Formasi Rohani pada setiap ranah pendidikan, menjadikan spirtualitas seseorang bergerak maju dan terus bertumbuh serta naik level. Artinya pendidikan yang berlangsung bukan hanya pengetahuan semata melainkan terdapat tindakan aktif untuk menjadi pelaku-pelaku Firman.Suatu formasi rohani yang diterapkan dalam kehidupan orang percaya, akan membantunya untuk mempertajam kerohanian serta kekuatan iman, sehingga mampu mengalahkan keinginan daging yang bertentangan dengan kehendak Bapa. Hal ini tentu bukan hanya sekadar respon melainkan praktik-praktik rohani yang terus dilatih dan dikerjakan dalam kehidupan sehari-hari. Jika tidak, maka akan mengalami stagnasi atau kekeringan rohani bahkan sampai kematian rohani. Penelitian ini menggunakan metode penelitian kualitatif dengan studi pustaka, di mana penulis akan mengelaborasi karak-teristik generasi Z melalui beragam pustaka yang mendukung, serta mengusulkan penerapan Pendidikan Agama Kristen Berbasis Formasi Rohani bagi generasi Z dalam mempersiapkannya menghadapi tantangan iman masa kini, sehingga diperoleh kesimpulan Implementasi Pendidikan Agama Kristen Berbasis Formasi Rohani adalah proses pengajaran atau pembelajaran yang berfokus pada penerapan disiplin rohani secara terus-menerus melalui pembimbingan dan pemu-ridan, dengan tujuan untuk memiliki karakter dan pribadi serupa dengan Yesus Kristus dalam kehidupannya sehari-hari.